2021
DOI: 10.3390/plants10050999
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Unreduced Gametes and Neopolyploids in Alfalfa: How to Fill the Gap between Well-Established Meiotic Mutants and Next-Generation Genomic Resources

Abstract: The gene flow mediated by unreduced gametes between diploid and tetraploid plants of the Medicago sativa–coerulea–falcata complex is pivotal for alfalfa breeding. Sexually tetraploidized hybrids could represent the best way to exploit progressive heterosis simultaneously derived from gene diversity, heterozygosity, and polyploidy. Moreover, unreduced gametes combined with parthenogenesis (i.e., apomixis) would enable the cloning of plants through seeds, providing a unique opportunity for the selection of super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…falcata), plants that produce unreduced female and male gametes were used for sexual polyploidization and breeding (Veronesi et al, 1986). The locus controlling 2n egg cell formation in two-n egg (tne), a spontaneous alfalfa mutant, has been identified; however, the TNE gene has not been cloned yet (Palumbo et al, 2021). Rhoades and Dempsey (1966) described a maize natural recessive mutant named elongate (el) because of the elongated appearance of the chromosomes at both meiotic anaphases, which produced unreduced embryo sacs, but reduced functional pollen grains.…”
Section: Meiotic Mutants Producing Unreduced Gametes In Sexual Speciesmentioning
confidence: 99%
“…falcata), plants that produce unreduced female and male gametes were used for sexual polyploidization and breeding (Veronesi et al, 1986). The locus controlling 2n egg cell formation in two-n egg (tne), a spontaneous alfalfa mutant, has been identified; however, the TNE gene has not been cloned yet (Palumbo et al, 2021). Rhoades and Dempsey (1966) described a maize natural recessive mutant named elongate (el) because of the elongated appearance of the chromosomes at both meiotic anaphases, which produced unreduced embryo sacs, but reduced functional pollen grains.…”
Section: Meiotic Mutants Producing Unreduced Gametes In Sexual Speciesmentioning
confidence: 99%
“…SMC5/6 mutants show an absence of chromosome segregation during the first and/or second meiotic division, producing 2 n gametes. A comparison of the well-established meiotic mutants in alfalfa with the genes identified from Arabidopsis showed that nine proteins belonging to A. thaliana known for their involvement in 2 n gamete production occurred in alfalfa, suggesting common lineage of genes implicated in 2 n gamete formation ( Palumbo et al, 2021 ). Molecular techniques, particular CRISPR/Cas9 could be used for engineering plants with increased production of either 2 n pollen or 2 n eggs and used for breeding of novel polyploid ornamental plants.…”
Section: Occurrence Of 2 N Gametes In Ornamental P...mentioning
confidence: 99%
“…However, the production of unreduced gametes with a somatic (2n) rather than a gametophytic (n) number of chromosomes has been observed in a wide variety of plant species (Harlan and de Wet, 1975;Kreiner et al, 2017a;Ramanna and Jacobsen, 2003). When those unreduced gametes participate in fertilization, polyploid offspring are produced in a process known as sexual polyploidisation (Palumbo et al, 2021). Unreduced gametes can result from a variety of cytological events that include pre-or post-meiotic genome doubling and several meiotic restitution mechanisms (de Storme and Geelen, 2013).…”
Section: Ploidy Reductionmentioning
confidence: 99%